The Effect Of Giving Red Dragon Fruit (Hylocereus polyrhizus) Extract On Spermatozo Motility In White Rats (Rattus norvegicus) Wistar Line With High Fat Induction - Kirani Nuranisa; Cut Fauziah; Yuli Suciati (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Hyperlipidemia is a condition when high level of blood lipids and causes morphological changes in spermatozoa. Red dragon fruit (Hylocereus Polyrhizus) is one of the plants as a source of antioxidants and has unsaturated fat content that is needed in the spermatozoa maturation process. The aims of this the study is to determine the benefits of red dragon fruit extract on the motility of white rat spermatozoa (Rattus norvegius) induced by high-fat diet. The study is design by true experimental research and research only testing group design. This research conducted in the Pharmacology and Therapy Laboratory, Padjajaran University Education Hospital, in January 2020 using white rats, male . ± 8 weeks wistar strains weighing ± 200-250. The study sample was divided into several groups such group I as a control, group II as a negative control, group III as positive group with simvastatin dose 0.72 mg / day, group IV as research group 1 using red dragon fruit extract dose of 60 mg / 200 grBB / day for 52 days, and group V as group 2 therapy using dragon fruit extract dose of 60 mg / 200grBB / day for 104 days. The results showed that the mean percentage of motility of rat spermatozoa increased in the relief group with the supplement of red dragon fruit extract by dosing of 60 mg / 200 grBB / day for 104 days, or 51, 2%. This study conclude that red dragon fruit has a superior effectivity better than simvastatin in increasing the motility of spermatozoa.